Effects in Trujillo derived from student events in Lima on May 23, 1923 (2018)
The present work has the purpose of studying the effects evidenced in the city of Trujillo, as a result of the events occurred on May 23, 1923 in Lima, within the student movement for the University Reform initiated in Argentina in 1918 and in Peru in 1919. It is the result of a research that uses a qualitative methodology with historical emphasis. The events occurred during the government of Augusto B. Leguía who, seeking his reelection and violating the Political Constitution, ordered the consecration of Peru to the Heart of Jesus. During the protest carried out by students of the University of San Marcos and workers of Lima, a student and a worker died as a result of the violent repression. The government arrested the movement leaders. These events were echoed at the University of Trujillo. The intransigence of the rector and the University Council created a strong tension. The students sketched concepts in accordance with the principles of the University Reform: university for change and open doors as the home of the people and for the people. The authorities did not exhibit any formative position, but compulsive and anachronistic; they responded with repression.14 students were expelled definitively and other 8, temporarily.